2019
DOI: 10.1002/jbm.a.36626
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium phosphate phases affecting the crosstalk between osteoblasts and osteoclasts in vitro

Abstract: Previous studies have reported that octacalcium phosphate (OCP) enhances osteoblast differentiation and osteoclast formation during the hydrolysis process to hydroxyapatite (HA). However, the crystal phases that affect the crosstalk between osteoclasts and osteoblasts are unknown, which should determine the bone substitute material's property of OCP. The present study was designed to investigate whether the chemical composition and crystal structure of calcium phosphates affect osteoclast formation and the ost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 69 publications
1
32
0
Order By: Relevance
“…This also supports the hydrolysis of OCP in SBF 33) . Such analysis also demonstrated that the hydrolysis of OCP for the conversion into HA had been induced in a cell culture medium supersaturated with respect to OCP and HA 30) . On the other hand, the transformation of OCP into HA in vivo has been confirmed by ultrastructural observation and crystallographic analysis 7,9) .…”
Section: Conversion Reaction and Apatite Formationmentioning
confidence: 91%
See 4 more Smart Citations
“…This also supports the hydrolysis of OCP in SBF 33) . Such analysis also demonstrated that the hydrolysis of OCP for the conversion into HA had been induced in a cell culture medium supersaturated with respect to OCP and HA 30) . On the other hand, the transformation of OCP into HA in vivo has been confirmed by ultrastructural observation and crystallographic analysis 7,9) .…”
Section: Conversion Reaction and Apatite Formationmentioning
confidence: 91%
“…This is because OCP incorporates Ca 2+ and releases Pi ions during the hydrolysis reaction 8) . The decrement or increment of these ions in the medium depends on the amount of OCP incubated 28,30,100) . Furthermore, the pH locally decreased at the area adjacent to the OCP surface of its granules in a Tris-HCl buffer containing F − , although the buffering effect occurs to maintain the pH under the physiological condition 101) .…”
Section: Ion Environment In Physiological Condition Regulated By Ca-psmentioning
confidence: 99%
See 3 more Smart Citations